2016
DOI: 10.3892/etm.2016.3441
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of therapeutic plasma exchange on monocytes in antiphospholipid syndrome

Abstract: Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by thrombosis and recurrent fetal loss, with the persistent presence of antiphospholipid antibodies (aPLs). aPLs exert their pathogenic effect via the overproduction of tissue factor and activation of complement and several cell types, including endothelial cells, platelets and notably monocytes. As a result, a hypercoagulable state develops leading to APS-associated obstetric complications and fetal loss. Despite being far from op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…The direct pathogenic role of aPL antibodies was demonstrated in animal models showing pregnancy loss and thrombus formation after the immunisation of animals with aPLs [45,46]. Another proof is evidence of the clinical improvement after the removal of autoantibodies by plasma exchange or plasmapheresis [47,48]. Our study shows the ability of patient-derived aPL to induce immune cell activation and contribute to the thrombotic events.…”
Section: Discussionsupporting
confidence: 56%
“…The direct pathogenic role of aPL antibodies was demonstrated in animal models showing pregnancy loss and thrombus formation after the immunisation of animals with aPLs [45,46]. Another proof is evidence of the clinical improvement after the removal of autoantibodies by plasma exchange or plasmapheresis [47,48]. Our study shows the ability of patient-derived aPL to induce immune cell activation and contribute to the thrombotic events.…”
Section: Discussionsupporting
confidence: 56%
“…Data on the effect of ALSSs on serum IL‐6 levels are controversial. Previous studies reported that TPE reduced the elevated serum levels of IL‐6 in patients with ALF, Martirosyan et al showed that TPE increased IL‐6 mRNA transcripts in monocytes from patients with antiphosphalipid syndrome, restoring the mRNA expression levels to within normal ranges, whereas Vanessa et al showed that FPSA and MARS failed to change serum IL‐6 levels significantly in patients with ACLF despite IL‐6 was removed by the two systems, and the discrepancy was probably due to a high rate of cytokine production in ACLF patients . However, few studies investigated the effect of TPE and DPMAS on serum levels of IL‐6 in ACLF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another evidence for the pathogenicity of autoantibodies was obtained in studies proving a substantial clinical improvement after the removal of autoantibodies by plasma exchange or plasmapheresis (8). Mechanistically, we demonstrated the restoration of monocyte transcriptional activity in patients with APS after plasmapheresis (9).…”
Section: Introductionmentioning
confidence: 89%